Peradilan Agama di Indonesia Pasca UU Nomor 50 Tahun 2009 Tentang Perubahan Kedua Atas UU Nomor 7 Tahun 1989 - Nursalam, Nursalam; Shuhufi, Muhammad; Sultan, Lomba (AHKAM, 2024)
This research aims to reveal and analyze the existence of Religious Courts as a robust and equal branch of judicial power alongside other courts, as regulated by the Judicial Power Law. Religious courts are one of the judicial bodies exercising judicial power to enforce law and justice for people seeking justice in specific cases involving Muslims, particularly in matters of marriage, inheritance, wills, gifts, endowments, zakat, infak, alms, and sharia economy. The factors supporting the existence of religious courts are based on changes in Law Number 7 of 1989 to Law Number 3 of 2006 and Law Number 50 of 2009 concerning Religious Courts. With these changes, the institutional existence of Religious Courts has been strengthened as their adjudicative authority has been expanded, making their institutional presence as solid as other courts. This expanded authority elevates the status of Religious Courts as a medium for maintaining their institutional existence. The hindering factors include the limited physical and non-physical facilities, such as human resources (HR) that are not evenly distributed in quality and quantity within the Religious Courts, and the fact that many judges in the Religious Courts do not yet fully master civil law and civil procedural law. The amendment of Law Number 50 of 2009 brought significant changes to the judiciary in Indonesia, including changes in the position and authority of religious judges. The position of judges post-amendment of Law Number 50 of 2009 is regulated by the Supreme Court, in accordance with Law Number 48 of 2009 concerning Judicial Power, which places Religious Courts alongside other courts under the Supreme Court. Additionally, the Judicial Commission exists to uphold the honor, dignity, and conduct of judges, providing external oversight of judges.